Breathing resistance in metabolic systems: Its effects on pulmonary ventilation and oxygen uptake in elite athletes with high aerobic power - Ainegren, M.; Jensen, K.; Rosdahl, H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
The aim of this study was to investigate the effects on pulmonary ventilation and oxygen uptake (VO2) in athletes with a very high maximal oxygen uptake (VO2max) and corresponding high ventilation capacity when using a modern metabolic system with relatively high resistance to breathing (HIGHRES), compared to a traditional system with low resistance to breathing (LOWRES). Four rowers and three cross-country skiers (without asthma), competing at a high international level, performed in experimental conditions with LOWRES and HIGHRES using a rowing ergometer and roller skis on a treadmill. The results showed that VO2, blood lactate, heart rate and respiratory exchange ratio were not different between the LOWRES and HIGHRES test conditions during both submaximal and maximal exercise. Also, the athlete`s time to exhaustion (treadmill) and mean power (rowing ergometer) from maximal tests were no different between the two conditions. However, ventilation and expiratory O2 and CO2 concentrations were different for both submaximal and maximal exercise. Thus, the authors have concluded that the differences in resistance to breathing of metabolic systems influence elite endurance athletes V.E at low to very high workloads, thus affecting the expired gas fractions, but not the submaximal VO2, VO2max and performance in a laboratory setting at sea level.